Environmental damage arising from oil operations in the Niger Delta region of Nigeria (2017)
The oil industry located within the NigerDelta región of Nigeria has contributed immensely to the growth and development of the nation’s economy over the past five decades but unsustainable oil prospecting, exploration, development and production activities have rendered this unique parí of the country one of the five most severely petroleum damaged ecosystems in the world. The Niger Delta consists of diverse ecosystems of mangrove swamps, fresh water swamps and rain forest. It is the largest wetland in Africa and among the ten most important wetland and marine ecosystems in the world. However, due to oil pollution arising from oil spillage and gas flaring the area is now characterized by contaminated streams and rivers, forest destruction and biodiversity loss. In general, the area is an ecological wasteland. This affeets the livelihood of the host communities who depend on the ecosystem Services for survival leading to increased poverty, adverse human health ejfects and socio-economic problems. The govemment has formulated legislations for protection of the environment from detrimental impaets of oil operations, but these musí be made effective in terms of implementation, enforcement and monitoring by responsible agencies. This paper discusses the several impaets that oil exploration and production have had on the environment of the Niger Delta Región of Nigeria, and examines the efforts made by the government and multinational oil companies to remedy the situation